Stress, Zoom Fatigue, and Learning Outcomes of Bachelor of Nursing Students in The Covid-19 Pandemic - Purba, Sri Dearmaita; Sijabat, Flora; Amila, Amila (Alta Dharma Publisher, 2022)
Introduction: Traditional learning has changed to online learning as an implication of the policy to prevent the transmission of the Covid-19 virus in Indonesia. Online learning is a new learning system in Indonesia that uses internet technology networks and can trigger stress and fatigue. Objective: The aim of this study is to determine the effect of online learning on stress, zoom fatigue, and student learning outcomes in undergraduate academic stage of nursing at Sari Mutiara University Indonesia, Prima Indonesia University, and Institute Health Sciences of Flora Medan. Method: The research design was a correlation analytic study with a cross sectional approach. The sampling technique used purposive sampling with the number of respondents as many as 211 people. Data collected through Google Forms which were sent to nursing students via WhatsApp. The data were analyzed by performing the Spearman correlation test with confidence coefficient at p <0.05. Result: The results showed that the majority of online learning was good (56.1%), the duration of online learning was >2 hours/day (62.7%), the internet connection was sometimes stable (72.2%, the student's stress level was moderate (45.9%). The majority of students' zoom fatigue was moderate (48.2%). The majority of nursing students' learning outcomes were cumlaude (65.9%). There was a relationship between online learning and stress levels (p = 0.037; r = -0.144), zoom fatigue (p = 0.049; r = 0.299), and learning outcomes for undergraduate nursing students (p = 0.005; r = 0.194). Recommendation: Lecturers need to innovate learning media and explore stress factors and their relationship with coping strategies in online learning is important for further research. Keywords: Covid-19, online, stress, fatigue, learning